ASC‐1 transporter‐dependent amino acid uptake is required for the efficient thermogenic response of human adipocytes to adrenergic stimulation. Issue 16 (23rd July 2021) - Arianti, Rini; Vinnai, Boglárka Ágnes; Tóth, Beáta B.; Shaw, Abhirup; Csősz, Éva; Vámos, Attila; Győry, Ferenc; Fischer‐Posovszky, Pamela; Wabitsch, Martin; Kristóf, Endre; Fésüs, László
Abstract : Brown and beige adipocytes dissipate energy by uncoupling protein 1 (UCP1)‐dependent and UCP1‐independent thermogenesis, which may be utilized to develop treatments against obesity. We have found that mRNA and protein expression of the alanine/serine/cysteine transporter‐1 (ASC‐1) was induced during adipocyte differentiation of human brown‐prone deep neck and beige‐competent subcutaneous neck progenitors, and SGBS preadipocytes. cAMP stimulation of differentiated adipocytes led to elevated uptake of serine, cysteine, and glycine, in parallel with increased oxygen consumption, augmented UCP1‐dependent proton leak, increased creatine‐driven substrate cycle‐coupled respiration, and upregulation of thermogenesis marker genes and several respiratory complex subunits; these outcomes were impeded in the presence of the specific ASC‐1 inhibitor, BMS‐466442. Our data suggest that ASC‐1‐dependent consumption of serine, cysteine, and glycine is required for efficient thermogenic stimulation of human adipocytes. Abstract :